Cation–π interaction assisted facile preparation of graphene/epoxy nanocomposites with superior strength and toughness. Issue 39 (28th July 2022) - Huang, Ying; Yan, Xin; Li, Xiaobo; Du, Mengqi; Li, Yicheng; Yuan, Rui; Yang, Li; Chang, Guanjun
Abstract: High‐performance graphene/epoxy nanocomposites are desired in many fields. However, the performance of graphene/epoxy nanocomposites is far from the actual demand, and many methods reported for the preparation of graphene/epoxy nanocomposites need the participation of environmentally harmful organic solvents. Herein, a novel, facile, and green cation–π interaction assisted phase transfer approach is developed for construction of graphene/epoxy nanocomposites. This strategy includes constructing potassium ion modified reduce graphene oxide (K‐rGO) as nanofiller and choosing 1‐(oxiran‐2‐ylmethyl)‐1H‐indole (IN) as phase transfer agent. The cation–π interaction is formed between K‐rGO and indole group, which not only facilitates the transfer of K‐rGO from water phase to organic phase, but also enhances the dispersion of K‐rGO in epoxy. When the loading of K‐rGO is 0.10 wt%, the tensile strength and elongation at break of epoxy nanocomposites increase by 116.6% and 126.5%, respectively, compared to neat epoxy. The simultaneous improvement in tensile strength and extensibility of graphene/epoxy nanocomposites is achieved. Furthermore, the prepared epoxy nanocomposites exhibit an excellent thermal conductivity owing to the good dispersion of K‐rGO in epoxy matrix. Abstract : The graphene/epoxy nanocomposites with superior strength and extensibility are prepared by using a green phase transfer method via cation–π interaction between IN and K‐rGO, where IN is used as phase transfer agent and K‐rGO is used as nanofiller. Additionally, the excellent thermal conductivity of graphene/epoxy nanocomposites is achieved at low filling.